Noncompliance with the Therapeutic Regimen: Contributing Factors - P. Thenmozhi (Perspective of Recent Advances in Medical Research Vol. 11, 2023)
The study aims to assess the factors contributing to noncompliance with follow-up care among post-cardiac patients. A cross-sectional research design was adopted with 50 samples that matched the inclusion criteria selected by the convenience sampling technique. Data on factors contributing to noncompliance was collected by using the checklist. The current study revealed that all physical, psychological, economic, social, and spiritual factors highly influenced noncompliance. Of these, the highest percentage was found in medication side effects, lack of accessibility and financial support, and low health literacy. Healthcare providers must focus on interventions to follow up to prevent readmission and lead a successful life.